Transcending invisible lanes through inclusion of athletics memories in archival systems in South Africa - Joseph Matshotshwane; Mpho Ngoepe (HTS Teologiese Studies/Theological Studies, 2022)
In countries like South Africa, sports have the power to transcend invisible lanes of politics and race and thus inspire citizens to come together. Sport, including athletics, has been demonstrated as an instrument of solidarity of fragmented cultures. However, while sport is of such significance, it is still minimally represented in public archival holdings in South Africa. Despite the mandate to transform the archival system, evidence suggests that much of the memories of sports heroes, especially that of athletes, have not been recorded. This qualitative study utilised oral history as a research method to explore the feasibility of building inclusive archives through the collection of sports memories. Athlete participants were identified through snowball sampling and data were collected using both oral testimony interviews from athletes with first-hand information and oral tradition augmented through document analysis. The results of the study indicated that there are stories and memories of many great South African distance runners that must be told and included in the archive repositories. Sadly, these stories have not been recorded in written words, as there is a tendency to perpetuate elitism by documenting mostly oral history of prominent members of society with political power. The study revealed that most of athletes’ memories from their running careers include certificates, trophies, medals, Springbok jerseys, newspaper clippings and pictures in their possession. It is concluded that until these sports archives and objects are considered as an important and unique element of South African history, they will forever be lost.